Norm entrepreneurship and diffusion 'from below' in international organisations: How the competent performance of vulnerability generates benefits for small states. Issue 4 (22nd March 2019) - Corbett, Jack; Xu, Yi-chong; Weller, Patrick
Abstract: For decades, the world's smallest states – the structurally weakest members of the multilateral system – have been considered incapable of influencing international organisations (IOs). So, why has the label small state risen to prominence over the last two decades and become institutionalised as a formal grouping in multiple IOs? Drawing on more than eighty in-depth interviews, we explain the rise of Small Island Developing States in the United Nations system, the expansion of their agenda to the Small and Vulnerable Economies group at the World Trade Organization, and then to other IOs. The adoption of the labels is evidence of small state norm diffusion. We identify the competent performance of vulnerability within multilateral settings as the key to explaining this norm emergence and diffusion. The lesson is that diffusion 'from below' is not always driven by a desire to increase rank. In this case small states have gained benefits by maintaining a lowly position in a hierarchy in which large is stronger than small.